The Compatibility of Donald Trump’s Reciprocal Tariff with WTO and Indonesia’s National Interests - Syariffudin, Muhammad Reza Zaki; Sadida, Muhammad Qaulan; Nugroho, Muhammad Adjie; Cason, Christopher Michael (Universitas Internasional Batam, 2025)
Donald Trump, President of the United States, implemented a reciprocal tariff international trade policy that aims to regulate commercial exchanges between countries. The reciprocal tariff policy has sparked controversy, where several countries have rejected this policy and considered it a violation of World Trade Organization (WTO) principles. Under this policy, countries deemed to have significant barriers to products originating from the United States will be subject to a minimum tariff of 10% with some countries are subject to much higher tariffs, such as Vietnam, which faces a 46%, including Indonesia which faces 32% increase in import tariffs to the United States. This study examines how Donald Trump’s Reciprocal Tariff policy aligns with World Trade Organization (WTO) principles and agreements, and how the Indonesian government has responded legally to this policy. The fundamental World Trade Organization (WTO) principles are based on non-discrimination, yet the tariffs imposed vary between countries. To determine the appropriate response, Indonesia must consider a strategic lens that balances risk, utility, and long-term national interest. By thoroughly analyzing these factors, this study aims to provide insights into the potential violations of World Trade Organization (WTO) principles by the tariff policy and recommend how Indonesia should respond effectively. Employing a normative juridical research method, the study combines statutory and case approaches, supported by secondary literature, and expert interviews. The findings show that the reciprocal tariff policy violates fundamental WTO principles, especially Most-Favored Nations principle under Article 1 GATT, tariff binding principle under Article II GATT, National Treatment principle under Article III GATT, and Publication and Administration of Trade Regulations provision under Article X GATT. The best legal steps that the Indonesian government can take in dealing with the reciprocal tariff policy is by initiating negotiation.